Efek Temperatur Kandang Berbeda Pada Perfoma Ayam Broiler - Nepa, Juliana Monika; Pamungkas, Aditya; Widu, Asri Apriana; Ottu, Melliany Anggelina; Sinabang, Maria Kristina (CV. SINAR HOWUHOWU, 2025)
This study aims to determine the effect of temperature on broiler chicken production. This study was conducted at the Dryland Lab, Faculty of Animal Husbandry, Maritime Affairs and Fisheries, Nusa Cendana University. The study was conducted for 28 days, divided into 1 week of adjustment and 3 weeks of data collection. The DOC chickens used were 1 week old with the CP 707 strain with a total of 100 chickens. The feed used was CP 11 and CP 12 feed. This study was an experimental study using a completely randomized design (CRD). This study consisted of 4 treatments and 5 replications with a total of 20 plots. Each plot contained 5 chickens. Treatments included T1 = Cage temperature 30-30.5°C, T2 = Cage temperature 32-32.5°C, T3 = Cage temperature 34-34.5°C, T4 = Cage temperature 36-36.5°C. The variables were feed consumption, PBB, FCR, and drinking water consumption. The data analysis used Analysis of Variance (ANOVA) and, if significant (P<0.05), was followed by Duncan's test. Statistical results showed that different cage temperatures significantly (P<0.05) affected feed consumption, PBB, and FCR, but not significantly (P>0.05) on drinking water consumption. It can be concluded that different temperatures affect broiler chicken perfomance.